Shallow soil slope instability analysis at horticultural farm, Daman, Central Nepal - Manandhar, Suman (Bulletin of the Department of Geology, 2008)
Slope stability analyses were carried out for slopes around the horticultural farm at Daman, Central Mahabharat Region of Nepal. Daman lies in the Mahabharat zone with intruded granite as the basement rock. These granites are highly to completely weathered and decomposed to few metres depth from the exposed surfaces. The horticultural farm is situated over these decomposed rocks with some colluvium along the hill slopes. The rainstorm of 19-21 July 1993 devasted the horticultural farm with numerous landslides and gully erosions. Based on the limit equilibrium analysis theory and computed index as well as strength properties of the soil, analyses of three of the failed slopes were carried out. The analyses revealed that slides were unstable only during fully saturated conditions. doi: 10.3126/bdg.v10i0.1422 Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 10, 2007, pp. 71-78